2019
DOI: 10.1101/19010199
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Gaze, Visual, Myoelectric, and Inertial Data of Grasps for Intelligent Prosthetics

Abstract: Hand amputation is a highly disabling event, having severe physical and psychological repercussions on a person's life. Despite extensive efforts devoted to restoring the missing functionality via dexterous myoelectric hand prostheses, natural and robust control usable in everyday life is still challenging. Novel techniques have been proposed to overcome the current limitations, among which the fusion of surface electromyography with other sources of contextual information. We present a dataset to investigate … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…The MeganePro dataset was acquired with the aim of investigating the use of gaze and visual information to improve prosthetic control (Cognolato et al, 2019). It contains data of 15 transradial amputees [13 M, 2 F; age: (47.13 ± 14.16) years] and a frequency matched control group of 30 able-bodied subjects [27 M, 3 F; age: (46.63 ± 15.11) years] who performed grasps and manipulation tasks with a variety of household items.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The MeganePro dataset was acquired with the aim of investigating the use of gaze and visual information to improve prosthetic control (Cognolato et al, 2019). It contains data of 15 transradial amputees [13 M, 2 F; age: (47.13 ± 14.16) years] and a frequency matched control group of 30 able-bodied subjects [27 M, 3 F; age: (46.63 ± 15.11) years] who performed grasps and manipulation tasks with a variety of household items.…”
Section: Methodsmentioning
confidence: 99%
“…The first fixation is defined as the first of at least two successive samples where the gaze-target distance is <20 px. This threshold was chosen to accommodate for some systematic error in the gaze tracking and is roughly twice the average gaze tracking accuracy (Cognolato et al, 2019). The requirement for two successive samples that fall below the threshold is to ignore occasional outliers.…”
Section: Methodsmentioning
confidence: 99%
“…While this study found that vision had an impact on predicting grasp poses, it is unknown whether gaze has the same impact on solely the wrist rotations. Cognolato et al [23] provides an approach towards grasp classification by using vision and gaze tracking on amputees that already use prosthetic hands in order to provide an improvement in creating pre-grasp hand poses. A large dataset was collected on both intact subjects and amputees, and provides gaze data, as well as myoelectric signals, and various learning algorithms were implemented for grasp classification.…”
Section: B Current Literaturementioning
confidence: 99%
“…Meanwhile, the skin wrapping around two bones realizes the tactile perception to the environment. Decades of efforts have brought about great progress on intelligent bionic prosthetic hand: in order to build the visual sensation substitution, the method of multimodal information fusion based on computer vision, inertial [3] and eyes tracking [4] was proposed to assist the manipulating of prosthetic hand. With the rich perception of RGBD camera and the excellent recognition of deep learning, the method of computer vision improved the grasping accuracy in the daily life scenarios [5,6].…”
Section: Introductionmentioning
confidence: 99%